Carvacrol attenuates amikacin-induced nephrotoxicity in the rats - Cemil Çolak; Ahmet Sefa Duman; Yılmaz Çiğremiş; Atta Mohammad Dost; Selahattin Tunç; Nigar Vardı; Azibe Yıldız; Onural Özhan; Hakan Parlakpınar; Mehmet Günata (Atatürk University, 2024)
Objective: Amikacin (AK) is a wide-spectrum antibiotic routinely used to treat gram-negative and some gram-positive bacterial infections. However, its use is limited due to its potential to cause nephrotoxicity due to an increase in reactive oxygen radicals. The main goal of this study was to investigate the effect of carvacrol (CAR) on AK-induced nephrotoxicity in rats. Methods: Thirty-two Sprague Dawley rats were randomly separated into four groups: the control (0.9% NaCl solution and sunflower oil), AK (400 mg/kg), CAR+AK (80 mg/kg CAR+400 mg/kg AK), and AK+CAR (400 mg/kg AK+80 mg/kg CAR) groups. AK and CAR were administered intramuscularly and orally, respectively for 7 days. Blood and kidney tissue samples were collected at the end of the experiment. The level of catalase, superoxide dismutase, malondialdehyde, and reduced glutathione, which are parameters of oxidative stress, were detected while comparing renal function and histopathological changes. Results: Histopathological findings (necrotic changes, dilatation and inflammatory cell infiltration) were significantly greater in the AK group than in the control group. Additionally, significant weight loss was detected in the rats in the AK group. CAR treatment, both before and after AK administration, significantly improved nephrotoxicity histopathologically (p<.05). However, the same improvement was not identified biochemically. Conclusion: CAR treatment significantly improved nephrotoxicity both before and after AK administration, suggesting that carvacrol has a protective effect against AK-induced kidney damage at the histopathological level.Keywords: Antioxidant, amikacin, carvacrol, nephrotoxicity, oxidative stress, rat